Extracapillary proliferation is an independent predictive factor in Immunoglobulin A nephropathy. (September 2015) - Serriello, Ilaria; Polci, Rosaria; Feriozzi, Sandro; Gigante, Antonietta; Di Giulio, Salvatore; Rosa, Margherita; Galliani, Marco; Morosetti, Massimo; Pugliese, Francesco; Petitti, Tommasangelo; Onetti Muda, Andrea; Giannakakis, Konstantinos
Abstract: Background: Oxford classification of Immunoglobulin A Nephropathy (IgAN) identifies four pathological features as predictors of renal outcome (MEST‐score): mesangial proliferation (M); endocapillary proliferation (E); segmental glomerulosclerosis (S); tubular atrophy/interstitial fibrosis (T). In particular extracapillary proliferation (Ex) was not considered as an independent histological variable predicting renal outcome. Recently the VALIGA study provided a validation of the Oxford classification in a large European cohort of IgAN patients and re‐stated that Ex is not associated with a worse renal prognosis. We propose a retrospective study to evaluate the predictive value of the MEST‐score in a multi‐centre, single region group of patients from central Italy and in addition, to investigate Ex as a marker predicting renal outcome. Methods: One hundred and seven patients were enrolled in this study. Clinical data of each patient were available at diagnosis and follow‐up. The median age at diagnosis was 36.7 years; 72% of the patients were males. Histological parameters were those included in the MEST‐score of the Oxford classification; in addition, Ex was also assessed. Results: Multiple linear regression models for survey were used. Statistical analysis showed a correlation between the progression of renal decline, in terms of estimated glomerular filtration rate (slope eGFR), and M, S, T. Differently from Oxford and VALIGA studies, no correlation was found with E, while Ex correlated with a decline of eGFR. Conclusions: Our results suggest that Ex represents an additional independent variable associated with a faster decline of renal function in IgAN. Summary at a Glance: In this manuscript, the authors evaluated the predictive value of the Oxford classification of IgA nephropathy in a multi‐centre, single region group of patients from central Italy and showed that extracapillary proliferation was an independent predictive factor of IgA nephropathy.